Ecological characteristic of hermit crabs in Lhokseumawe mangrove forest, Aceh, Indonesia - Fitriani, Fitriani; Erlangga, Erlangga; Syahrial, Syahrial; Ezraneti, Riri (Universitas Malikussaleh, 2024)
The study was conducted between August and September of 2021 in order to determine the density, ecological index, distribution pattern, geographic distribution, environmental factors, and the relationship between hermit crabs and environmental factors. Hermit crabs were gathered using a quadratic transect and sample plots, while environmental variables were measured in situ. PCA and CCA multivariate statistics were used to determine the characteristics and correlation between hermit crabs and environmental factors. Hermit crabs were discovered to be comprised of two species (Clibanariuslongitarsus and C. infraspinatus) and one family (Diogenidae), with the highest density found in the C. longitarsus species (1.22 ± 0.57 - 4.68 3.53 ind/m2), diversity index is categorized as moderate (2.0<H‰¤3.0), the dominance is low (0<C‰¤0.5), the distribution pattern is clustered (IÎ´>1), the geographical distribution is abundant (>80%), and environmental factors are categorized as good. In addition, Stations I and II have high DO, TOM, mangrove density, C. longitarsus, and C. infraspinatus parameters, whereas Station III has high salinity, pH, and temperature, with salinity, mangrove density, and TOM being the most influential parameters on hermit crab density.